2012
DOI: 10.1155/2012/962683
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Intussusception due to Metastasized Sarcomatoid Carcinoma of the Lung: A Rare Cause of Intestinal Obstruction in Adults

Abstract: Although small bowel intussusception is one of the most common abdominal emergencies in childhood, it is rare in adults and usually occurs as a result of an underlying pathology. Sarcomatoid carcinoma, a very rare subtype of lung cancer, rarely metastasizes to small bowel and causes complications. In this paper, we aim to describe a patient with small bowel intussusception caused by an isolated small bowel metastasis of the sarcomatoid carcinoma of the lung by reviewing the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…49,50 Rare cases of testicular seminoma, 51 osteosarcoma, 52,53 and Ewing sarcoma 54 have also been described. Symptoms of intestinal metastasis described in the literature include intussusception, 16,[20][21][22][23][24][25][26][27][28][29][43][44][45][46][47][48][49][50][51][52][53][54] and perforation [17][18][19][30][31][32][33][34][35][36][37][38][39][40][41][42] . The curative treatment of ATC is multimodal and consists of surgery and external beam radiation therapy with radio-sensitizing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Rare cases of testicular seminoma, 51 osteosarcoma, 52,53 and Ewing sarcoma 54 have also been described. Symptoms of intestinal metastasis described in the literature include intussusception, 16,[20][21][22][23][24][25][26][27][28][29][43][44][45][46][47][48][49][50][51][52][53][54] and perforation [17][18][19][30][31][32][33][34][35][36][37][38][39][40][41][42] . The curative treatment of ATC is multimodal and consists of surgery and external beam radiation therapy with radio-sensitizing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The hematogenous route appears to be the most likely means of spread [7]. Some authors have even suggested a lymphatic route through the thoracic duct [8].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of these metastases is more than expected [ 10 ] particularly in patients with longer survival [ 7 , 1 , [10] , [11] , [12] , [13] , [14] ]. The path of metastatic diffusion is still controversial ; although hematogenous way appears to be the most likely [ 14 ], other Authors suggested a lymphatic diffusion through the thoracic duct [ 15 ]. The onset of symptoms depend on localization [ 14 ] and invasion of the intestinal wall [ 16 ]; dysphagia, anemia, abdominal pain, melena, nausea, vomiting and weight loss are the most commonly complained symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most cases complications such perforation, bleeding and occlusion [ 11 , 8 , [16] , [17] , [18] , [19] ] reveal abdominal metastases. Bleeding generally occurs in upper or lower intestinal tract sites [ [13] , [14] , [15] , [16] ], and is a sign of necrosis of the bowel wall, while occlusion and perforation are more frequent in the small intestine [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. Intussusception with consequent occlusion [ 15 , 26 , 27 ] has also been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation